BRIDGING CULTURE AND CONCEPTS: EXPLORING STATISTICS COMPETENCY THROUGH JAVANESE WAYANG CULTURE - Sari, Dela Yulanda; Marsigit (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2025)
The purpose of this study was to determine how the application of wayang culture facilitated the abstraction abilities of junior high school students in learning statistics. The participants of this study were eighth-grade students from a junior high school in Baran Village. Data collection techniques included observation, exploration, tests and interviews. The results of this study indicate that the fundamental mathematical aspects found in wayang can be implemented in contextual mathematics learning for junior high school, especially in statistics material. This conclusion is reinforced by the test results where 75% of participants obtained correct answers with scores above 85. This study implies that wayang culture-based learning has strong potential for application in formal mathematics education in schools.